Does Urban Concentration/Dispersion Affect Immigrants' Professional Opportunities? (The case of Porto Metropolitan Area) - Emília Malcata Rebelo (2010)
This article aims to test the hypothesis that urban concentration/dispersion characteristics exert an influence on the social and professional attainment levels reached by different immigrant groups in northern Portugal. I propose a theoretical and empirical methodology for analysing the impact that concentrated or dispersed neighbourhoods exert on immigrants' social and professional opportunities. The latter are assessed in terms of professional success, and a relationship is established between the professional levels reached by different immigrant groups and the territorial characteristics inherent to each group, as well as current concentration/dispersion patterns of land use. I also design an integrated information system to monitor the access of different population groups to professional opportunities, and to support municipal decisions in matters of immigrants' social, economic and cultural integration. Then I discuss how joint territorial planning policies, urbanization processes, ethnic features, the labour and housing markets and sociological assimilation networks have performed in Portugal's northern region in general, and the Porto metropolitan area in particular, both in launching local strategic economic development and in successfully integrating immigrants within the professional socio-economic fabric..